Telaah Singkat Tentang Pendidikan Kristen Menurut Pernyataan Gravissimum Educationis - Sarang, Rikardus Kristian (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2013)
This article provided short explanation about Christian Education which included on the Konsili Vatikan II document, Greavisimmum Educationis. This document underlined some point of view about the Church position in the relationship with education world. Church giving full and intensively supported in order to make the education touched by all elements of society with its rights. In this document, not only giving chance to society to take education as wide as possible, but also proposed the teacher and educator people to dedicate their ability wholy to improve children’s achievement. The Church greatly paid attention toward the youth’s education, because they are the churchmen of tomorrow. Through the holy Consili, Catholic Church wanted to stress out the increasing of human resources which started from the perfect education process by keep holding humans right. Eduction must become the main menu in spiritual life, in order to raise up the properous and happyness for all society